Energy expenditure and dietary intake in professional female football players in the Dutch Women`s League: Implications for nutritional counselling - Brinkmans, N.; Plasqui, G.; van Loon, L.; van Dijk, J.-W. (Journal of Sports Sciences, 2024)
In contrast to male football players, research on the nutritional requirements of female football players is limited. This study aimed to assess total daily energy expenditure (TDEE) in professional female football players, along with body composition, physical activity and dietary intake. This observational study included 15 professional football players playing in the highest Dutch Women`s League. TDEE was assessed by doubly labelled water over 14 days, along with resting metabolic rate (RMR; ventilated hood), fat-free mass (FFM; dual-energy x-ray absorptiometry), and dietary intake (24-h recalls). Physical activity energy expenditure (PAEE) was derived from subtracting RMR and estimated diet-induced thermogenesis (10%) from TDEE. TDEE was 2882 ± 278 kcal/day (58 ± 5 kcal/kg FFM) and significantly (p < 0.05) correlated with FFM (r = 0.62). PAEE was 1207 ± 213 kcal/d. Weighted energy intake was 2344 kcal [2023-2589]. Carbohydrate intakes were 3.2 ± 0.7, 4.4 ± 1.1 and 5.3 ± 1.9 g/kg body mass for rest, training and match days, respectively, while weighted mean protein intake was 1.9 ± 0.4 g/kg body mass. In conclusion, the energy requirements of professional female football players are moderate to high and can be explained by the substantial PAEE. To fuel these requirements, sports nutritionists should consider shifting the players` focus towards prioritizing adequate carbohydrate intakes, rather than emphasizing high protein consumption.